2014
DOI: 10.1182/asheducation-2014.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Clinically defining and managing high-risk pediatric patients with acute lymphoblastic leukemia

Abstract: For children with acute lymphoblastic leukemia, the identification of those at higher risk of disease recurrence and modifying therapy based on this risk is a critical component to the provision of optimal care. The specific definitions of high-risk ALL vary across cooperative groups, but the themes are consistent, being largely based on leukemia biology and disease response. Intensification of conventional chemotherapy for those with high-risk disease has led to improved outcomes. It is anticipated that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 91 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…The list of genetic alterations in childhood ALL that are associated with the risk of relapse continues to grow. Ph chromosome, BCR - ABL1 like with IZKF1 and JAK2 alterations, MLL rearrangements, hypodiploidy (< 44 chromosomes or DNA index < 0.81), and iAMP are assigned as unfavorable characteristics [24]. In contrast, hyperdiploidy with trisomy 4 and 10 and ETV6 - RUNX1 fusion are designated favorable genetic factors [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of genetic alterations in childhood ALL that are associated with the risk of relapse continues to grow. Ph chromosome, BCR - ABL1 like with IZKF1 and JAK2 alterations, MLL rearrangements, hypodiploidy (< 44 chromosomes or DNA index < 0.81), and iAMP are assigned as unfavorable characteristics [24]. In contrast, hyperdiploidy with trisomy 4 and 10 and ETV6 - RUNX1 fusion are designated favorable genetic factors [24].…”
Section: Discussionmentioning
confidence: 99%
“…Ph chromosome, BCR - ABL1 like with IZKF1 and JAK2 alterations, MLL rearrangements, hypodiploidy (< 44 chromosomes or DNA index < 0.81), and iAMP are assigned as unfavorable characteristics [24]. In contrast, hyperdiploidy with trisomy 4 and 10 and ETV6 - RUNX1 fusion are designated favorable genetic factors [24]. The results of G-banding analysis in the patient showed that the primary leukemia cells had 3 gross structural chromosomal abnormalities, namely, trisomy 8, and 9p and 17p deletions, but no unfavorable characteristics at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 3 5 This classification informs the selection of an appropriate treatment strategy, whereby those stratified into the SR and MR subtypes are treated with less intensive chemotherapy, while more aggressive protocols are reserved for those exhibiting an HR subtype. 6 8 …”
Section: Introductionmentioning
confidence: 99%